(3JaSjQ GdYScQjs - (3GdMSjfj GdgGTej, CHh eMeO, GdnMnSf GdNGpdU, GdMSf Hf Ydj GdgGOj Hf eMeO GdLhGO, J(B260(3g`s ((3Ydj GdTHJQjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B...(3bGd cGfG CHhGfG EeGejjf hcGfJ GdRjOjI ge GdZGdHhf HESJQGHGP(B...s
(3BNQgG (B:s
(3hjfJgj YfO JaSjQ bhdg JYGdi (B{ (3hdG jCHi GdTgOGA EPG eG OYhG(B} (3bGdhG fRdJ ajef EPG OYj dSeGY GdTgGOI CHi, hCfRdf ajef GeJfY Yf COGA GdTgGOI EPG cGfJ YfOg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B200s
(3GdPQjYI(B:(3L(B4(3,U(B207(3,Qbe(B1295s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs